Anthropogenic impact in the Santa Maria di Leuca cold-water coral province (Mediterranean Sea): Observations and conservation straits. (November 2017) - D'Onghia, G.; Calculli, C.; Capezzuto, F.; Carlucci, R.; Carluccio, A.; Grehan, A.; Indennidate, A.; Maiorano, P.; Mastrototaro, F.; Pollice, A.; Russo, T.; Savini, A.; et al.
Abstract: The Santa Maria di Leuca (SML) cold-water coral (CWC) province is a proposed priority conservation area according to several conservation initiatives in the Mediterranean Sea. Part of it is a Fisheries Restricted Area (FRA). Anthropogenic impacts due to fishing on this FRA were investigated using a towed camera system during 2005. The geographic distribution of fishing effort in the SML CWC province was examined through an observers' program of longline and trawl fishing activities during 2009 and 2010 and Vessel Monitoring by satellite System (VMS) data from 2008 to 2013. Using the video system, it was possible to observe evidence of impacts in the FRA due to longlines, proved by remains of lines on the bottoms and/or entangled in corals, and those due to trawl nets, proved by trawl door scars on the bottom. The application of Generalized Liner Models indicates that the impacts due to longline were significantly related to a geographic site characterized by carbonate mounds while those from trawl net were significantly related to the soft bottoms, consisting of bioturbated fine-grained sediments. The presence of waste of various types was also observed in the FRA; plastic was the most widespread waste and was significantly related to a macrohabitat characterized by the presence of corals. The geographic distribution of fishing effort for each type of fishing were rather superimposed in the two years of the observers׳ program and six years of VMS data with a significantly greater fishing effort outside the FRA than inside this area. The trawlers generally fished on the muddy bottoms of the upper and middle slope within the SML CWC province and near and inside the northward limit of the FRA. The longliners fished mainly on the shelf in north and off the FRA. The coral by-catch was only recorded during 2009 in 26% of the trawl hauls. No coral by-catch was recorded from longlining in either year. The catches from longlining mainly consisted of Chelidonichthys lucerna, Merluccius merluccius and Conger conger while those from trawling mostly consisted of Aristeus antennatus, Aristaeomorpha foliacea and M. merluccius . The information collected during the observers׳ program and VMS data indicated greater impact due to trawling than longlining. The conservation and effective management of this vulnerable marine ecosystem remain difficult.